Males' Ability to Report Their Partner's Contraceptive Use at Last Sex in a Nationally Representative Sample: Implications for Unintended Pregnancy Prevention Evaluations. (May 2017) - Garbers, Samantha; Scheinmann, Roberta; Gold, Melanie A.; Catallozzi, Marina; House, Lawrence; Koumans, Emilia H.; Bell, David L.
Addressing and enabling the role of males in contraceptive choices may facilitate efforts to reduce unintended pregnancy rates and disparities in the United States, but little is known about males' ability to report their partners' contraceptive use. Data from the 2011-2013 National Survey of Family Growth from 2, 238 males aged 15 to 44 years who had vaginal sex with a noncohabiting or nonmarital partner and were not seeking pregnancy were examined to tabulate the proportion of males able to report whether their partner used a specific contraceptive method use at last sex (PCM) by sociodemographic and sexual history characteristics. Logistic regression was used to assess odds of being unable to report PCM, adjusting for age and sexual history factors. Most (95.0%) were able to report PCM, with no difference by age group (chi-square = 7.27, p = .281) in unadjusted analyses. Males with a new sex partner (14.8% of the sample), compared with those with an established sex partner, had significantly higher odds of being unable to report PCM in bivariate (11.7% vs. 3.7%, chi-square = 39.39, p < .001) and multivariable (adjusted odds ratio [AOR]: 3.17, 95% confidence interval [CI: 1.74, 5.65]) analyses. Those whose last sexual encounter was more than 3 months ago also had higher odds of being unable to report in bivariate ( OR : 1.74, 95% CI [1.05, 2.87]) and multivariable analyses (AOR: 2.04, 95% CI [1.04, 4.03]). Most men were able report PCM, but reporting was significantly lower among men with new sex partners. To inform future research and evaluation relying on male report, validation studies comparing male report with partner report, specifically among new couples, are needed.